2021
DOI: 10.3390/ijerph19010189
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Associations among Heavy Metals with Red Blood Cell Hemogram

Abstract: This study aimed to investigate gender differences in the association between heavy metals and hemograms including hemoglobin (Hgb), mean corpuscular volume (MCV) and mean corpuscular hemoglobin concentration (MCHC). A health survey of 2447 participants was conducted in southern Taiwan between June 2016 and September 2018. Seven heavy metals were measured: blood lead (Pb), urine nickel (Ni), urine chromium (Cr), urine manganese, urine arsenic (As), urine copper and urine cadmium (Cd). The results show that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The high concentrations of Mo in plasma and urine in male soccer players could facilitate the formation of uric acid, avoiding the damage of free radicals (superoxide anions) generated by xanthine oxidase in the ischemia–reperfusion processes generated during high-intensity physical exercise [ 53 ]. In relation to the above, uric acid concentrations appear to be higher in active men [ 54 ] and male athletes [ 55 ]. In addition, women seem to be less susceptible to oxidative stress, particularly premenopausal women, due to the antioxidant role of estrogen [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high concentrations of Mo in plasma and urine in male soccer players could facilitate the formation of uric acid, avoiding the damage of free radicals (superoxide anions) generated by xanthine oxidase in the ischemia–reperfusion processes generated during high-intensity physical exercise [ 53 ]. In relation to the above, uric acid concentrations appear to be higher in active men [ 54 ] and male athletes [ 55 ]. In addition, women seem to be less susceptible to oxidative stress, particularly premenopausal women, due to the antioxidant role of estrogen [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…These date indicate that different job types are exposed to diverse hazard factors. BCu of women tends to be 15% to 17% higher than that of men 21 . The results of the recent research showed that the higher concentrations of Cd were observed in men and those of Sn were observed in women (Table 4); combined with another study, 22 in healthy non–occupational hazard exposure people, the blood concentration of Cd was higher in men compared with women, whereas tin was higher in women ( P < 0.05).…”
Section: Discussionmentioning
confidence: 82%
“…BCu of women tends to be 15% to 17% higher than that of men. 21 The results of the recent research showed that the higher concentrations of Cd were observed in men and those of Sn were observed in women (Table 4 ); combined with another study, 22 in healthy non–occupational hazard exposure people, the blood concentration of Cd was higher in men compared with women, whereas tin was higher in women ( P < 0.05). It has been hypothesized that estrogen-induced ceruloplasmin synthesis in the liver may lead to an increased Cu in blood.…”
Section: Discussionmentioning
confidence: 82%
“…The median for E Cd /E cr in women enrolled in the NHANES 1988-1994 was 0.77 µg/g creatinine, higher than that of men (0.58 µg/g creatinine) [34]. A study from Taiwan, including 977 men and 1470 women (mean age 55), reported a mean urinary Cd concentration higher in women than men (0.9 vs. 0.7 µg/L) [35]. A study from Sweden observed higher blood Cd in women than men of a similar age [36].…”
Section: Exposure Levels Of Concernmentioning
confidence: 95%
“…This practice simply reflects the fact that universally women have a lower muscle mass, and thus lower E cr , compared to men. For the same reason, the normalisation of Cd excretion to E cr yields typically higher E Cd /E cr values in women, compared to men of similar age [34][35][36][37].…”
Section: Impact Of Normalisation Of Urinary Excretion Rates Of Cadmiu...mentioning
confidence: 99%